The Museum as Experience Learning, Connection, and Shared Space - Shifrin, Susan (Collection Development, Cultural Heritage, and Digital Humanities, 2023)
Museums have long been viewed as exclusive, excluding, and as antiseptic to intimacy. In the past few decades, however, humanized experiences-cultivated by curators, educators, artists, activists, and marketers alike-have emerged as the reason for being for these cornerstones of community. Such experiences are often possible only in museum settings, where cultural exploration, probing conversation, and safe risk-taking can occur in spaces now becoming sacred through inclusiveness. This book brings together an interdisciplinary collection of essays examining the kinds of human experiences and interactions that have converted the once-sterile museum into a space of enlivenment and enrichment, as well as physical and emotional well-being. The essays focus for the first time on the uniquely human and humanizing experiences to be found in the collections, programs, exhibitions, and spaces of today's museums.